Circular Supplier Sourcing and Performance of Manufacturing Companies in Kenya - Athiambo, Agnes Ayako; Omwenga, Jane; Namusonge, Eric (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study evaluated the influence of circular supply supplier sourcing on the performance of manufacturing companies in Kenya. The research was guided by the specific objectives: to determine the effect of circular supplier sourcing on performance of manufacturing companies in Kenya and to assess the moderating effect of circular supply chain reconfiguration on the relationship between circular supplier sourcing and performance of manufacturing companies in Kenya. The theoretical framework was underpinned by Systems theory and Strategic choice theory. Methodology: Employing a cross-sectional survey design, the study targeted 795 manufacturing companies in Kenya, excluding the service sector, as per the 2023 KAM directory. A sample of 266 companies was drawn using Slovin's formula and stratified sampling technique. Data was collected using questionnaires. Quantitative data was analyzed using both descriptive and inferential statistics and with the help of SPSS version 27. Regression analysis was used to show the relationship between the dependent variable and the independent variable and the study employed multiple linear regression analysis to test the hypotheses. Findings: Key findings revealed that circular supplier sourcing had significant positive effects on company performance and supply chain reconfiguration demonstrated a significant moderating effect on the relationship between circular supplier sourcing and company performance. These findings contribute to understanding circular economy principles in the Kenyan manufacturing context and provide valuable insights for practitioners and policymakers in implementing circular supply chain management practices. Unique Contribution to Theory, Policy and practice: Thus, the study recommends that manufacturing firms should put into consideration circular supplier sourcing practices to improve performance in market share, sales volume and return on investment levels. Future research directions include a longitudinal study to examine the long-term effects of circular supplier sourcing practices on manufacturing performance and a comparative study of circular supplier sourcing practices across different industries in Kenya to identify sector-specific challenges and opportunities.